PENGARUH SUBSTITUSI TEPUNG KACANG ALMOND DENGAN TEPUNG KACANG KEDELAI TERHADAP SIFAT FISIK DAN DAYA TERIMA MARZIPAN - Azizah, Dinda Marifatul; Singamurni, I Gusti Ayu Ngurah; Alsuhendra (Jurnal Sains Boga, 2024)
This study aims to analyze the effect of soybean flour substitution on marzipan making on physical properties and consumer acceptability. This research was conducted at the Pastry and Bakery Laboratory of the Culinary Education Study Program, Faculty of Engineering, State University of Jakarta. The sample in this study was soybean flour substitution marzipan with a percentage of 50%, 60%, 70%. This research was conducted with an experimental method, namely testing the density and acceptability of consumers conducted on 30 rather trained students of the Culinary Education Study Program with assessment aspects including aspects of color, sweetness, aroma, softness, stickiness, and elasticity. The results of the density value study were analyzed using calipers and digital scales that showed the substitution of soybean flour in marzipan with a percentage of 0% having a high density of 1.27 g / cm3. The consumer acceptance test analyzed by the Friedman test showed that there was no influence on the aspects of color, sweetness, aroma, softness, and stickiness which resulted in the substitution of soybean flour in marzipan with a percentage of 70% preferred, but there was an influence on the aspect of elasticity so that continued with the Tuckey's test which resulted in the substitution of soybean flour in marzipan with a percentage of 70% preferred by the panelists.